Ensuring the quality and accreditation of higher education institutions in Libya In light of the experience of both the United States of America and Canada (Economic studies journal, 2021)
Abstract     The present study aimed to identify the for most prominent features of systems quality assurance and accreditation of higher education institutions in (the U S A), and (Canada), This is to benefit from it in guiding the development of quality systems and accreditation of higher education institutions in Libya, in a manner that is commensurate with its environment and the system of quality assurance and accreditation of Libyan higher education institutions.     To achieve the objectives of the study, relied on the comparative approach, which passes several steps: first, to provide a theoretical framework derived from previous literature on quality assurance systems and accreditation of higher education institutions in both the United States and Canada, By presenting the philosophy on which these systems are based and the most important basic principles for them, and the most important quality assurance and accreditation bodies and its mechanisms were presented. The second step comes through a comparison between the two systems, to reach the third step, which is a presentation of a vision and recommendations for the most important lessons learned from the two previous systems for the development of a system for quality assurance and accreditation of higher education institutions in Libya.
Keywords: Quality Assurance; Accreditation; Higher Education